PLAN ESTRATÉGICO DE MARKETING PARA LA COMPAÑÍA DE TAXIS EJECUTIVOS “TRANS PEÑA SUR S.A. DE LA CIUDAD DE LOJA, PERIODO 2015-2020 - Ríos Villa, John Vinicio (2016)
The main objectives of the research were to perform an external diagnosis, internal diagnostics of the functional area of marketing, conduct a competitive analysis, carry out a market study and propose a proposed strategic plan for the organization; this research is based on a Framework theoretical and conceptual framework. Regarding the research methodology they were used the following methods: Deductive, Inductive and Synthetic; and two techniques are mainly applied: The Interview and Survey, information was collected and assessed by different matrices (MEFE, MEFI, MPC). As for the results, then the external analysis was found among his main opportunities elimination of safeguards imposed on the tires and the ordinance that allows units have ten years of useful vita; Among its main threats are the uncertainty generated by the increase in taxi fare and increased informal competitors. The internal analysis identified their strengths and their outstanding technical quality of service and availability to combine services; likewise its most prominent as a lack of market research, lack of publicity and low market share weaknesses were identified. Once all culminated market analysis and research, we proceeded to make the SWOT matrix which created a list of strategies according to the consistency of internal and external factors; the proposed strategic plan for the company under study where the proposed business philosophy, organizational structure, policies for the fulfillment of the plan, growth opportunities, value proposition, strategic map is also performed, the results allowed four objectives clearly defined 5 strategic plan, which are to increase the use of the service of the company by 30% by 2020, taking advantage of new information technologies; make an advertising plan and carry out promotions in order to improve the competitive position of the company until 2020; establish strategic alliances with suppliers to reduce operating costs and allow companies to increase the clientele of the company; and achieve excellence in the quality of customer service and periodically monitor the activities of all employees. Each objective has its individual plan and its budget. Finally it is concluded that the taxi service is in an environment of opportunities; from the five selected companies company under study is in fourth place; predominate weaknesses to strengths in the area of marketing; only 5% of users recall having made use of the services of the company "Trans South Peña" and the company hopes to attract more customers through the implementation of the plan indicted on strategies that enable the company to develop selectively and improve.